2018
DOI: 10.31393/morphology-journal-2018-24(3)-08
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the sizes of the kidney after contralateral nephrectomy in the experiment

Abstract: The evaluation of renal measurements such as length, width and thickness, volume is important in the diagnosis and treatment of many renal disorders, since there is a close relationship between the sizes of the kidneys and its function. The purpose of the study was to establish and compare during the postoperative period changes in the mass and sizes of the kidney left after nephrectomy in the sexually mature male rats. An experimental study was carried out on 84 sexually mature white male rats weighing 178-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…evaluated the changes in kidney size after nephrectomy in mice and found that animals undergoing nephrectomy had a significant increase in kidney size. [ 22 ] In our study, we found that based on sonography, the kidney size increased significantly during the study, but no changes in the variables related to renal function including eGFR, creatinine, urine Ca/Cr, and urine Pr/Cr were seen. Therefore, according to the study by Monastyrskyi et al .…”
Section: Discussionmentioning
confidence: 54%
“…evaluated the changes in kidney size after nephrectomy in mice and found that animals undergoing nephrectomy had a significant increase in kidney size. [ 22 ] In our study, we found that based on sonography, the kidney size increased significantly during the study, but no changes in the variables related to renal function including eGFR, creatinine, urine Ca/Cr, and urine Pr/Cr were seen. Therefore, according to the study by Monastyrskyi et al .…”
Section: Discussionmentioning
confidence: 54%